Analisis Hasil Belajar Siswa Pada Mata Pelajaran IPAS Dengan Menggunakan Model Problem Based Learning (PBL) Kelas IV SD Inpres Porame - Ara, Mutiara; Kaharu, Sarintan N.; Khairunnisa, Khairunnisa; Satria Dewi Pendit, Sinta (Primary School Teacher Education Study Program; Faculty of Teacher Training and Education; Tadulako University, 2023)
AbstractMutiara, 2024. Analysis of Student Learning Outcomes in IPAS Subjects Using the Problem Based Learning (PBL) Model for Class IV SD Inpres Porame. Thesis elementary school teacher education program, department of education science, faculty of teacher training and education science, tadulako university. Supervisor Sarintan N. Kaharu, S.Pd., M.Pd. The problem in this study is the low student learning outcomes in IPAS subjects, it can be seen from the daily test scores, where out of 33 students only 10 people scored above the KKM, which is 70. The purpose of this study was to analyze student learning outcomes with the problem-based learning model in class IV SD Inpres Porame. This type of research is descriptive qualitative research in accordance with Bogdan and Taylor Nugrahani's research. The subjects of this study were fourth grade students of SD Inpres Porame, with 33 students. Data collection consists of observation sheets, interviews, documentation, and tests. Based on student learning outcomes in IPAS subjects with plant body parts material using the Problem Based Learning (PBL) model can be seen from the tests found to be 81.8%, student learning outcomes on a very good rating scale and there are 18.2%, student learning outcomes on a less good rating scale. This is due to the different learning styles of students. KeywordsStudent Learning Outcomes, IPAS subjects, Problem Based Learning (PBL) Model, Abstrak Mutiara, 2024. Analisis Hasil Belajar Siswa Pada Mata Pelajaran IPAS Dengan Menggunakan Model Problem Based Learning (PBL) Kelas IV SD Inpres Porame. Skripsi program pendidikan Guru sekolah dasar, jurusan ilmu pendidikan, fakultas keguruan dan ilmu pendidikan, universitas tadulako. Pembimbing Sarintan N. Kaharu, S.Pd., M.Pd. Masalah pada penelitian ini yaitu rendahnya hasil belajar siswa pada mata pelajaran IPAS, dapat dilihat dari nilai ulangan harian, dimana dari 33 siswa hanya 10 orang yang memperoleh nilai di atas KKM, yaitu 70. Tujuan penelitian ini adalah untuk menganalisis hasil belajar siswa dengan model problem based learning kelas IV SD Inpres Porame. Jenis penelitian ini adalah penelitian kualitatif deskriptif sesuai dengan penelitian Bogdan dan Taylor Nugrahani. Subjek penelitian ini yaitu siswa kelas IV SD Inpres Porame, dengan jumlah siswa 33 orang yang. Pengumpulan data terdiri dari Lembar observasi, wawancara, dokumentasi, dan test. Berdasarkan hasil belajar siswa pada mata pelajaran IPAS dengan materi bagian tubuh tumbuhan yang menggunakan model Problem Based Learning (PBL) dapat dilihat dari tes yang ditemukan sebesar 81,8%, hasil belajar siswa pada skala penilaian sangat baik dan terdapat 18,2% , Hasil belajar siswa dalam skala penilaian kurang baik. Hal itu disebabkan karena gaya belajar yang berbeda antara peserta didik. Kata KunciHasil Belajar Siswa, Mata Pelajaran IPAS, Model Problem Based Learning (PBL)